Clinical Efficacy and Safety Evaluation of a Monopolar Radiofrequency Device with a New Vibration Handpiece for the Treatment of Facial Skin Laxity: A 10‐Month Experience with 64 Patients. Issue 1 (15th November 2012) - Edwards, Arden Fredeking; Massaki, Ane Beatriz M. N.; Fabi, Sabrina; Goldman, Mitchel
Abstract : Background: Although ablative laser technology and surgical treatment are considered to be the criterion standard for the rejuvenation of aging skin, the demand for procedures with less down time and risk, such as nonablative laser and radiofrequency (RF) treatments, has increased over the last several decades. Objectives: To investigate the efficacy and safety of the newest generation of monopolar RF (mRF) devices by evaluating our patients after treatment. Methods and Materials: Sixty‐four patients with mild to moderate facial skin laxity were treated using the new mRF with vibration handpiece. Patients were surveyed between 1–10 months after treatment to determine degree of improvement, satisfaction, and presence of side effects. Results: With the new system, 80% ( n  = 51) reported at least mild correction of skin laxity, 55% ( n  = 35) noticed skin texture improvement, average pain level was 6.06 (0–10 scale), 9% ( n  = 6) found the procedure too painful, and 43% ( n  = 28) would have the procedure again. Conclusion: The new mRF system was safely tolerated and efficacious for most patients for facial treatment sites.